Use of Strict Patient Selection Criteria to Achieve Significant Surgical Outcomes from a Low DIEP Flap Breast Reconstruction - Cha, Han Gyu; Kang, Min Kyu; Han, Hyun Ho; Kim, Eun Key; Eom, Jin Sup (Journal of Reconstructive Microsurgery, 2019)
Background The low deep inferior epigastric perforator (DIEP) flap was first introduced in 2016 as it had aesthetic advantages over the conventional DIEP flap. With our experience of over 100 low DIEP flap procedures to date, we have conspicuously lowered complication rates and established more definitive criteria to select proper candidates.Methods We analyzed 103 patients who underwent breast reconstruction with the low DIEP flap at our hospital between May 2014 and June 2018. Demographics, patient selection criteria, flap specifics, surgical outcomes including postoperative complications, and the location of the abdominal scar and umbilicus were reviewed retrospectively.Results The mean patient age was 46.7 years, and the average body mass index was 23.7 kg/m2. A low DIEP with an average weight of 377 g was utilized within 6 hours 17 minutes in this cohort. There was no significant difference in the rate of venous congestion or fat necrosis compared with the conventional DIEP flap. The average distance from the pubic hairline to the abdominal scar was 0.6 cm and from the anterior superior iliac spine to the abdominal scar was −0.4 cm. The postoperative location of the umbilicus was 7.0 cm above the pubic hairline.Conclusion The low DIEP flap is not only a reliable option for a breast reconstruction but is an aesthetically superior approach with a lower abdominal scar and natural umbilicus. Patients may benefit from this technique if prudently selected by computed tomography (CT) angiography. A perforator that is larger than 1 mm in diameter and well enhanced on CT angiography from the division of the external iliac artery to the abdominal skin particularly in the intramuscular course should be selected.
Keywords: breast reconstruction; DIEP flap; donor-site scar